A preliminary estimation method of Los Angeles abrasion value of concrete aggregates - Tunc, Esra Tugrul; Alyamac, Kursat Esat (Elsevier Sci Ltd, 2019)
The main purpose of this study is to develop a preliminary estimation method to predict the Los Angeles abrasion value of concrete aggregates. For this purpose, Los Angeles abrasion tests were performed on the concrete aggregates which were basalt, waste marble and limestone. Five different number of iron balls (6, 12, 18, 24, and 30) in fixed diameters and four different number of revolutions of drum (500, 1000. 1500, and 2000) were used in these tests. After obtained the test results, the response surface method (RSM) was used to investigate the combine effect of the test parameters on the Los Angeles abrasion values. The variables are the number of iron balls, number of revolutions for drum, average saturated surface-dry aggregate density and average water absorption for RSM analysis. As a result, a preliminary estimation method was developed to classify the aggregates according to Los Angeles abrasion values. The developed method can be used to estimate the abrasion values approximately, practically and quickly. (C) 2019 Elsevier Ltd. All rights reserved.
Keywords: Los Angeles abrasion loss; Aggregate; Concrete; Response surface method